An orthopantomographic study of prevalence of hypodontia and hyperdontia in permanent dentition in Vadodara, Gujarat - Harleen Kaur Soni; Manjiri Joshi; Hina Desai; Mansi Vasavada (Wolters Kluwer Medknow Publications, 2018)
Background: Developmental anomalies in the number of teeth can result from disturbances in the developing dental lamina of the tooth. The dental lamina may become hyperactive leading to the formation of a supernumerary tooth or may fail to proliferate leading to the congenital absence of a primary or permanent tooth. Aims: The aim of the study was to assess the prevalence and distribution of hypodontia and hyperdontia in permanent dentition, excluding the third molars in children in Vadodara, Gujarat. Setting and Design: A descriptive, analytical, and cross-sectional study was conducted to determine the above-mentioned aims. Materials and Methods: In the study, panoramic radiographs of 1816 children (967 girls and 849 boys), aged 8 to 14 years were recorded and inspected for anomalies in the number of teeth. Statistical Analysis Used: The data was analyzed using SPSS version 10.00 (Statistical Package for the Social Sciences, Chicago, USA). Descriptive statistics and Chi-square-test were used to compare the results. The level of significance was set at 0.05. Results: The prevalence of hypodontia was 11.01%, and the most frequently absent tooth was the maxillary lateral incisor. There was an increased prevalence of hypodontia in females and in the mandibular arch of the permanent dentition. The prevalence of hyperdontia was 2.97% and the most common supernumerary tooth was mesiodens. There was an increased prevalence of hyperdontia in males and in the maxillary arch of the permanent dentition. Conclusions: There was a high prevalence of hypodontia and a low incidence of hyperdontia in the studied population. Prompt diagnosis of these anomalies can help plan treatment modalities at an early age to establish a functional and esthetic dentition.